WHAT DRIVES ELECTRONIC MEDICAL RECORD ADOPTION IN PRIVATE HOSPITALS: AN IMPORTANCE-PERFORMANCE MAP ANALYSIS (IPMA) - Lee, Jemimah Kezia; Antonio, Ferdi (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This study examined which factors are considered important and have performed well from the perspective of health workers in private hospitals in order to be utilised in EMR adoption for hospital performance. This research method uses PLS-SEM to obtain reliability and validation, followed by IPMA with SmartPLS4TM. This study was conducted using purposive sampling with 205 respondents consisting of nurses, general practitioners, specialists, dentists, and others. The PLS-SEM analysis confirmed that all organisational factors, namely Management Support, Patient Safety Climate, Adequate Training, Physician’s Involvement, Physician’s Autonomy, and Patient Relationship, related to EMR adoption, with Perceived Usefulness and Perceived Ease of Use as mediating variables. The Importance-Performance Map Analysis (IPMA) highlighted key areas for improvement. Patient Safety Climate indicators performed well and should be maintained. However, despite being highly important, Management Support (MANSU3) and Patient Relationship (PATREL4) indicators showed low performance. Stronger leadership engagement in EMR implementation and better patient education on its benefits is recommended. Overall, this study underscores the need for enhanced managerial support and improved communication strategies to optimise EMR adoption. By addressing low-performing but high-priority areas, hospitals can improve the quality of care to the patients, patient trust, and healthcare service quality through effective EMR integration.